2005
DOI: 10.1159/000088407
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Human Skin Permeation and Topical Anaesthetic Activity of a New Amethocaine Microemulsion

Abstract: We developed a fast-acting, topical, 4% (w/w) amethocaine microemulsion and tested its in vitro permeation in isolated human skin. Comparison with a commercial amethocaine gel (Ametop® ) was performed using Franz diffusion cells. Permeability coefficient (kp), flux (J) and percentage permeation after 10 h of microemulsion application were, in all cases, 1.5 times higher than those of the gel. The values obtained for the P1 parameter [1], 1.06·10<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…8a-d. Draize patch test is a reliable method and the results obtained from this study can be linked to those obtained in humans (Biruss and Valenta 2008;Kantarci et al 2007;Escribano et al 2005). The skin irritation studies indicated that MBG containing ITTN resulted in less irritation as compared to marketed ITTN formulation (Sotret Ò gel) after 72 h of application (Table 6).…”
Section: Skin Irritation Testingsupporting
confidence: 52%
See 1 more Smart Citation
“…8a-d. Draize patch test is a reliable method and the results obtained from this study can be linked to those obtained in humans (Biruss and Valenta 2008;Kantarci et al 2007;Escribano et al 2005). The skin irritation studies indicated that MBG containing ITTN resulted in less irritation as compared to marketed ITTN formulation (Sotret Ò gel) after 72 h of application (Table 6).…”
Section: Skin Irritation Testingsupporting
confidence: 52%
“…This phenomenon has been hypothesized in some investigations (Biruss and Valenta 2008;Kantarci et al 2007;Escribano et al 2005). Though the flux value of ITTN-based gel (0.0265 ± 0.0017 lg/cm 2 /h) is lesser than marketed ITTN gel (0.0284 ± 0.0047 lg/cm 2 / h), the difference is not significant (P [ 0.05).…”
Section: Development and Evaluation Of Microemulsionbased Gelmentioning
confidence: 70%
“…Finally, Tween -80 and propylene glycol were selected as an ideal surfactant and co-surfactant for the system. [15][16] Optical transparency: Optical transparency of the formulation was determined by inspecting the sample in clear and transparent container under the presence of good light against reflection into the eyes, and viewed against black and white illuminated background.…”
Section: Selection Of Surfactants and Co-surfactantsmentioning
confidence: 99%
“…Using human skin, Escribano et al have shown that 4% amethocaine microemulsions prepared with decane, water and lauromacrogol 300, produced a 1.5-fold higher flux and permeability coefficient value than commercially available gels [92] . The same authors suggested that these microemulsions promoted the skin deposition and flux of amethocaine via enhanced partitioning into the skin rather than by increasing their diffusivity in skin.…”
Section: Local Anaesthetic Agentsmentioning
confidence: 99%